2005
DOI: 10.1080/00268970500099925
|View full text |Cite
|
Sign up to set email alerts
|

Conformational equilibrium of formanilide: detection of the pure rotational spectrum of the tunnellingcisconformer

Abstract: 2005)Conformational equilibrium of formanilide: detection of the pure rotational spectrum of the tunnelling cis conformer, Formanilide has been investigated by molecular beam Fourier transform microwave spectroscopy. The rotational spectra of two conformers, with the formyl hydrogen cis or trans with respect to the phenyl group have been measured. Their relative energy has been estimated to be 350 AE 150 cm À1 , the trans form being more stable. In the cis species the plane of the pseudo-peptidic group forms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
32
1
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 18 publications
(32 reference statements)
6
32
1
2
Order By: Relevance
“…This result is consistent with previous molecular beam experiments 55,60,61 but is quite different from observations in microwave and solution experiments reporting a roughly equal population of both rotamers at room temperature. 54,56,67 Interestingly, the calculations suggest that the planarity of the amide group and its coplanarity with the phenyl ring are not much affected by the microhydration of the amide group in FA + −(H 2 O) n , in line with the high torsional barriers for both internal rotations.…”
Section: Articlementioning
confidence: 84%
See 1 more Smart Citation
“…This result is consistent with previous molecular beam experiments 55,60,61 but is quite different from observations in microwave and solution experiments reporting a roughly equal population of both rotamers at room temperature. 54,56,67 Interestingly, the calculations suggest that the planarity of the amide group and its coplanarity with the phenyl ring are not much affected by the microhydration of the amide group in FA + −(H 2 O) n , in line with the high torsional barriers for both internal rotations.…”
Section: Articlementioning
confidence: 84%
“…61 These values are in accordance with the theoretical predictions. 54,56,61,62,68 Isomer-selective IR spectra of t-/c-FA recorded in the hydride stretch (amide A, ν NH , ν CH ) and fingerprint (amide I−II) ranges demonstrate the large structural differences of the amide groups in the two isomers. 59,60 Interestingly, clusters of FA with polar (L = H 2 O) and nonpolar ligands (L = Ar) have so far only been observed for the more stable t-FA rotamer.…”
Section: Introductionmentioning
confidence: 99%
“…The angle between the amide and the phenyl ring in the cis configuration defined as the dihedral angle C 1 -N-C 2 -C 3 was found experimentally to be 34.7. 22 The trans configuration is planar.…”
Section: Introductionmentioning
confidence: 97%
“…17,18 Formanilide (N-phenylformamide, C 7 H 7 NO, see Scheme 1) is a formamide derivative which presents a cis-trans conformational equilibrium. [20][21][22] In fact, a MB-FTMW study has shown that both forms of formanilide are present in the supersonic expansion being the trans conformer most stable by ca. 350 cm 1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation